Healthcare providers’ knowledge, attitude, and practice towards cervical cancer screening in Sub-Saharan Africa: systematic review and meta-analysis - Delie, Amare Mebrat; Bogale, Eyob Ketema; Anagaw, Tadele Fentabel; Tiruneh, Misganaw Guadie; Fenta, Eneyew Talie; Endeshaw, Destaw; Eshetu, Habitu Birhan; Adal, Ousman; Tareke, Abiyu Abadi; Kebede, Natnael (Frontiers in Oncology, 2024)
Introduction: Cervical cancer is a prevalent cancer among women in low and middle-income countries, but it can be largely prevented through screening programs and HPV vaccination. This study aimed to determine the level of knowledge, attitudes, and practices regarding cervical cancer screening among healthcare providers in Sub-Saharan African countries.Methods: Systematic review and meta-analysis were conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Relevant databases including PubMed, Cochrane Library, AJOL, Google Scholar, and ScienceDirect databases were used to retrieve and search articles. The study included published and unpublished research written in English between January 2013 and May 16, 2024 for studies reporting knowledge, attitude, and practice towards cervical cancer screening among healthcare providers in Sub-Saharan Africa. This review has been registered on PROSPERO. The heterogeneity of the data was evaluated using the I 2 statistic. A meta-analysis was conducted using STATA 17 software, with a 95% confidence interval. The researchers also conducted publication bias and sensitivity analysis.Results: The review included 30 studies involving 7542 healthcare providers. The pooled magnitude of good knowledge status towards cervical cancer was 67.93% (95% CI: 53.36-82.50) whereas the pooled magnitude of positive attitude towards cervical cancer was 55. ). The results also showed that about 49.68% (95% CI: 33.18-66.17) of healthcare providers had good knowledge status about cervical cancer screening, 66.63%(95% CI: 50.36-82.89) had a positive attitude towards it, and only 17.23% (95% CI; 6.08-28.37) had ever screened for cervical cancer.The overall magnitude of knowledge and attitude of healthcare providers in Sub-Saharan Africa towards cervical cancer and its screening was suboptimal. Furthermore, a low percentage of female healthcare providers in the region had undergone screening for cervical cancer. As a result, policymakers and program administrators should focus on improving the knowledge, attitude, and practices of healthcare providers to meet the global health goal of cervical cancer screening and effectively eliminating cervical cancer.Healthcare providers must serve as role models for other women who should also undergo screening.